Temperature-dependent polar lignification of a seed coat suberin layer promoting dormancy in Arabidopsis thaliana - Lena Hyvärinen; Christelle Fuchs; Anne Utz-Pugin; Kay Gully; Christian Megies; Julia Holbein; Mayumi Iwasaki; Lara Demonsais; Maria Beatriz Capitão; Marie Barberon; Rochus B. Franke; Christiane Nawrath; et al. (Proceedings of the National Academy of Sciences, 2025)
The seed is a landmark plant adaptation where the embryo is sheltered by a protective seed coat to facilitate dispersion. In Arabidopsis , the seed coat, derived from ovular integuments, plays a critical role in maintaining dormancy, ensuring germination occurs during a favorable season. Dormancy is enhanced by cold temperatures during seed development by affecting seed coat permeability through changes in apoplastic barriers. However, their localization and composition are poorly understood. This study identifies and investigates a polar barrier in the seed coat’s outer integument (oi1) cells. We present histological, biochemical, and genetic evidence showing that cold promotes polar seed coat lignification of the outer integument 1 (oi1) cells and suberization throughout the entire oi1 cell boundary. The polar oi1 barrier is regulated by the transcription factors MYB107 and MYB9. MYB107, in particular, is crucial for the lignified polar oi1 barrier formation under cold temperatures. The absence of the oi1 barrier in mutant seeds correlates with increased permeability and reduced dormancy. Our findings elucidate how temperature-induced modifications in seed coat composition regulate dormancy, highlighting the roles of suberin and lignin in this process.